Comparison Of The Efficiency Of ZISWAF Fund Management At Amil Zakat Institutions In Indonesia - Putri, Sania Ramellia; Amir, Faizal (Jurnal Ekonomi, 2024)
This research aims to analyze and compare the level of efficiency of ZISWAF fund management in seven LAZs for the 2020-2022 period in Indonesia. This research includes descriptive quantitative research sourced from secondary data in the form of financial reports using the DEA analysis method. The results of this research show that in the 2020-2022 period, there are three LAZs, namely LAZ RZI, LAZ DDR, and LAZ AA which are in stable condition with an efficiency score of 100%. Meanwhile, four LAZs such as LAZISNU, LAZ LMIUI, LAZ YGYD, and LAZ YMAI tend to experience fluctuations with efficiency scores of less than 100%. The main cause of the inefficiency of the four LAZs is that funds have not been collected and distributed to the target optimally. Meanwhile, operational costs, personnel, and total assets are the second cause because they have a higher value, especially in general and administrative costs, basic amil rights and allowances, cash and cash equivalents, receivables, and advances for fund distribution activities when compared to a particular year. when achieving efficiency. So to be able to achieve the maximum level of efficiency, input variables need to be suppressed and output variables must be maximized.